Perlindungan Hukum Korban Kekerasan Dalam Rumah Tangga (KDRT) - Bima Guntara; Ayni Suwarni Herry; Ari Widiarti (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Domestic violence is an act of violence against women that is often invisible. Along with the increasing cases of domestic violence, the government issued a law on the Elimination of Domestic Violence, with the aim that victims of domestic violence, especially women, are expected to obtain legal protection. The problem that arises then is how to legally protect victims of Domestic Violence (KDRT) to prevent domestic violence crimes. The existence of Law Number 23 of 2004 concerning the Elimination of Domestic Violence is expected to be able to provide legal protection for victims of Domestic Violence (KDRT) significantly. The forms of protection provided for in this Law are temporary protection from the police, court protection and placement of victims in "safe houses". Criminal enforcement, which is the purpose of the domestic violence law, often has negative impacts on victims, including: divorce and domestic disharmony. Regarding forms of violence, violence is not solely physical in nature such as: beatings, persecution or torture that easily leave visible evidence. In many ways violence always takes many forms at once many dimensions. Psychological violence such as constant fear, receiving threats, making a person feel humiliated, is another form that is very difficult to prove but leaves a long mark in everyone's memory